Comparison of oropharyngeal airway dimensional changes in patients with skeletal Class II and Class III malocclusions after orthognathic surgery and functional appliance treatment: A systematic review - Feras AlQahtani; Jeny Mary George; Khaled Bishawi; Sam Thomas Kuriadom (Saudi Dental Journal)
Objective: To compare the dimensional changes in the oropharyngeal airway in patients with skeletal Class II and Class III malocclusion before and after orthognathic surgery and treatment with a functional appliance. Methods: The protocol was developed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P) and was registered to the International Prospective Register of Systematic Reviews (PROSPERO) under the registration number CRD42020170901. Furthermore, the reporting of the present SR was performed based on the PRISMA checklist. Results: The use of removable functional appliances increased the volume of the oropharyngeal airway in patients with skeletal Class II malocclusion. Furthermore, the increase in the volume of the oropharyngeal airway following the removable functional appliance treatment was more than that observed after fixed functional appliance treatment in growing patients. For patients with skeletal Class III malocclusion, who underwent the bimaxillary orthognathic surgery, resulted in no change in the dimensions of the oropharyngeal airway. Conclusion: Growing patients who receive removable functional appliance treatment have a more favorable long-term prognosis with regard to the oropharyngeal airway when compared with those who receive fixed functional appliance. Alternatively, in patients aged from (18–22) years with skeletal class III malocclusion Bimaxillary orthognathic surgery was found to be the recomended and superior method of treatment.